Investigating the role of discrete emotions in silence versus speaking up. Issue 3 (2nd May 2017) - Kirrane, Melrona; O'Shea, Deirdre; Buckley, Finian; Grazi, Adele; Prout, Joanne
Abstract : Silence in the workplace is a highly prevalent behaviour, but more is needed to understand the causes and consequences of such behaviour. In this article, we draw on theory and research to examine the role of discrete emotions in decisions to remain silent or to speak up. Three studies with full‐time employees were carried out utilizing both qualitative and experimental methodologies. Study 1 ( n  = 110) demonstrated that there are many reasons for being silent and established fear as the main emotion associated with silence behaviour. Building on the results of Study 1 and using a quasi‐experimental vignette design, Study 2 ( n  = 142) confirmed that different silence motives provoke different emotional experiences. Exploring the behavioural effects of emotions using a further experimental design, Study 3 ( n  = 80) showed that anger is an antecedent to speaking up about an observed transgression, whereas less intense anger was associated with staying silent. This pattern was not evident for fear. Taken together, these three studies provide empirical data regarding the relationship between silence, emotions, and actions. We contribute to theory and research at the intersection of silence, emotions, and behaviour and offer valuable insights into the dynamics of these concepts in the workplace. Practitioner points: Our study demonstrates that employees are silent for many reasons and that managers need to be sensitive to the multiple motives driving silence behaviour Managers need to be aware that silence provokes specific emotions, with fear and anger being particularly common emotional consequences of silence. Employees are more likely to take action when emotions are intense and so managers need to incorporate a sensitivity to employee emotions in understanding worker silence and voice